Minuus itseyden kiertoradalla : Hermann Hessen proosatekstit ja jungilainen psykoenergetiikka - Kulmala, Teppo (2001)
The study The Ego on the Orbit of the Self - Hermann Hesse 's Prose and the Jungian View of Psychoenergetics (Minuus itseyden kiertoradalla -Hermann Hessen proosa tekstit ja jungilainen psykoenergetiikka) focuses on that which occurs as psychic energy in Hesse's prose, as understood in terms of Carl Gustav Jung's analytical psychology. Hesse's works - from Demian (1919) to Das Glasperlenspiel (1943, English titles Magister Ludi and The Glass Bead Game) - attempt to define the forms of both the unconscious and the conscious and also to experience them. The archetypal language moves forward in cycles as a developing spiral circle that equals the process which Jung calls individuation. Events are "complexes" invollving psychic energy which are generated into consciousness together with the unconscious, "texts" with which it is easier for man to understand the projections of the unconscious and the assimilation of them into consciousness as a compensating experience. Archetypes, which man understands as collective symbols, create shapes, situations, phenomena and personifications that transform psychic energy. The "magical theatre" in Der Steppenwolf (English title Steppenwolf) and the "archive" in Die Morgenlandfahrt (English title A Joumey To The East) serve as examples of the psyche's complexes that involve psychic energy. These complexes are intemalized, and partially cognized, by means of symbolism. In Siddhartha, for example, projection is targeted at the symbol of the river. Siddhartha assimilates the energy of this syrnbol and experiences polar dynarnics as a river in him. As creative energy, this symbols compares to the cycle of nature. In Das Glasperlenspiel the regressive drowning of Josef Knecht - a man specialized in concepts - in a mountain lake symbolizes progression of the symbol phenome on as assimilation of the text into nature, an archetypal cycle. Projections and symbolism have an effect on man and cornmunity, and can even change them. In Hesse's works, main characters are created by using impulses from dreams, myths, arts and religions. The ego is challenged to participate in the creative work. This is individuation, and it affects the community through individuals, as exemplified by the life of Josef Knecht in Das Glasperlenspiel. Individuation resembles a heroic myth. Jung sees the archetypal symbols of the shadow, anima (and animus), the old wise man (and the great mother) and the self as the key phases of this myth. This study observes texts using these development phases as tools. The self, the psyche as a whole, is the source and the goal of every phase. Hesse's prose can be perceived as that which occurs, which interprets the possibilities of the ego to make the self become real on both individual and collective level. The inner goal is conceptualized on a relative level only. The texts have a function of expressing by means of relativity. As polar counterparts move towards each other in order to be unified, the energy of symbols can, however, be directed. Polar interaction is the key driving power in Hesse's texts.